Landslides Risk Analysis on Pacitan – Ponorogo National Road Section of East Java Province - Achmat Insana Masruchi Indroyono; Aji Suraji; Agus Tugas Sudjianto (Widyagama University of Malang, 2021)
Landslide is a natural event that at this time the occurrence is increasing. Landslide natural disasters can occur due to land use patterns that do not follow the rules of environmental sustainability, such as deforestation and the collection of natural resources that exceed their carrying capacity. This research was obtained that the threat, vulnerability of landslides on the national road section of Pacitan - Ponorogo obtained from the results of risky analysis is a very high risk. The result of the risk of very high level of Landslide is found at km 13+900 - 14 +000, km 12+500 - 12+600, km 27+201 - 28+051, km 27+200 - km 27+300, km 33+300 - 33+500, km 12+500 - 13+500. The level of Landslide risk on the Pacitan – Ponorogo National road is very varied, some are medium risk, medium risk, high risk to very high risk. Landslide handling techniques on the National road section of Pacitan - Ponorogo to be more effective and efficient because the conditions and value of Landslide risk are different, it will be better to handle in accordance with the level of Landslide risk in each location.